2008
DOI: 10.3174/ajnr.a1274
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Delay–Insensitive Algorithm Can Improve Reliability of CT Perfusion Imaging for Cerebrovascular Steno-Occlusive Disease: Comparison with Quantitative Single-Photon Emission CT

Abstract: BACKGROUND AND PURPOSE:Reliability of CT perfusion (CTP) algorithms has not been fully validated. We investigated whether the cerebral blood flow (CBF) values obtained by using a dynamic CTP technique with a tracer delay-insensitive deconvolution algorithm are more accurate than those obtained by using CTP with delay-sensitive algorithms in unilateral cerebrovascular steno-occlusive disease, when compared with those generated by quantitative single-photon emission CT (SPECT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 16 publications
1
38
0
Order By: Relevance
“…It does not matter if the reference is a mixture of GM and WM as long as the GM/WM ratio is nearly constant among diŠerent subjects by including a certain amount of volume in the reference. Most recently, Sasaki and associates demonstrated that CBFratio referencing to the healthy hemisphere was better than the absolute CBF obtained with cSVD, even by CT perfusion, 34 for intersubject comparison among ischemic patients. Chen also demonstrated that the rescaling approach for SVD and the Fourier Transform-based method using CBF=22 mL/100 cc/min of normal WM reduced error in CBF except for MTT dependency.…”
Section: D) Vascular Modelmentioning
confidence: 99%
“…It does not matter if the reference is a mixture of GM and WM as long as the GM/WM ratio is nearly constant among diŠerent subjects by including a certain amount of volume in the reference. Most recently, Sasaki and associates demonstrated that CBFratio referencing to the healthy hemisphere was better than the absolute CBF obtained with cSVD, even by CT perfusion, 34 for intersubject comparison among ischemic patients. Chen also demonstrated that the rescaling approach for SVD and the Fourier Transform-based method using CBF=22 mL/100 cc/min of normal WM reduced error in CBF except for MTT dependency.…”
Section: D) Vascular Modelmentioning
confidence: 99%
“…Horizontally in the tiles the MTT was varied (24,12,8 Prior to analysis, the slices in the phantom were filtered with a two-dimensional (2-D) Gaussian kernel with a standard deviation of 2.5 pixels. No additional filtering was applied.…”
Section: Digital Perfusion Phantommentioning
confidence: 99%
“…A previous study also reported that bSVD underestimates quantitative CBF values, presumably due to image noise. 24 More quantitative methods could lower the variability in CTP measurements due to observers, scanners, acquisition protocols, reconstruction methods, and analysis software. This may in turn result in more robust predictions of infarct core and penumbra, and minimizing the need for situation-specific thresholds and other software-calibration.…”
Section: Clinical Datamentioning
confidence: 99%
“…4,13,14,22 Different corrective functions for partial-volume effects (inaccurate measurements of contrast media concentration that occur due to the small size or location of cerebral vessels) cause significantly different CT perfusion results. 25 Computed tomography perfusion software that uses a corrective technique called vascular pixel elimination was found to more closely correlate with PET results than software that does not incorporate this technique.…”
mentioning
confidence: 99%